Comparative Effects of High vs Low Frequency of Static Stretching on Hamstring Flexibility in Diplegic Cerebral Palsy Children - Ayesha Tabassum; Farjad Afzal (Journal Riphah College of Rehabilitation Sciences, 2020)
Background: Cerebral Palsy the movement disorder due to brain injury results in muscles spasticity as well. Spasticity is well managed by stretching exercises. This study was a pre-post analysis of the effects of high frequency over sustained hamstring stretching of low frequency and how it decreases popliteal angle in diplegic cerebral palsy children.